Improving thermal stability and revealing physical mechanism in n-type Mg3Sb2-xBix for practical applications. (May 2023) - Shang, Hongjing; Zou, Qi; Zhang, Lin; Liang, Zhongxin; Song, Shaowei; Hong, Bin; Gu, Hongwei; Ren, Zhifeng; Ding, Fazhu
Abstract: N-type Mg3 Sb2- x Bi x alloys exhibit good potential for applications in waste-heat harvesting due to their high thermoelectric performance. However, recent studies have suggested that these materials suffer from high-temperature performance degradation, and the physical mechanism affecting their stability remains vague, both of which significantly limit their practicability. Here we focus on the thermal stability of Mg3 Sb2- x Bi x compounds, as well as the underlying physical mechanism. By adding cationic Co and Er into the matrix materials, both the electrical conductivity and Seebeck coefficient of Mg3 Sb2- x Bi x barely decline over 100 h of thermoelectric properties measurement at 673 K, indicating improved thermal stability, and the Mg3 Sb2- x Bi x compounds doped with Co and Er demonstrate thermoelectric performance comparable to that of Mg3 Sb2- x Bi x doped only with anionic Te. These findings indicate that enhancing the thermal stability of these materials does not result in their sacrificed thermoelectric performance. Additionally, the electron localization function is used to explore the underlying mechanism via density functional theory calculations, through which greater bonding strength is found between Co/Er and Sb/Bi in comparison with that between Mg and Sb/Bi, explaining the absence of high-temperature thermoelectric performance degradation for Mg3 Sb2- x Bi x doped with Co and Er. This study provides a new viewpoint for investigating the thermal stability of Mg3 Sb2- x Bi x materials, as well as for possible future studies on the thermal stability of other thermoelectric materials. Graphical Abstract: ga1 Highlights: Mg3 Sb2- x Bi x doped with Co&Er demonstrate thermoelectric performance comparable to that of materials doped only with Te. Both σ and S of Mg3.09 Er0.01 Co0.1 Sb1.5 Bi0.5 barely decline over 100 h of electronic property measurement at 673 K. Co and Er co-doped Mg3 Sb2- x Bi x possesses both high performance and good stability. Electron localization function (ELF) was first used to analyze the binding characteristics of Mg3 Sb2- x Bi x compounds.